USAGE OF PASTICHE GENRE IN INTERTEXTUAL PRACTICE OF ADVERTISING MEDIA DISCOURSE - D. Khrabskova; I. Tomicheva (Гуманитарные и юридические исследования)
Foreign language learning presupposes the acquisition of language code but it is also an entrance to a new communicative community which is culturally defined by its verbal genre. Access to knowledge is an admission to scientific communities which have their own discursive forms for presentation, discussion and allocation of knowledge. The educational activity is responsible for learners’ perception of “discursive fusion” which is a process of education. Contemporary higher school learners ought to master discursive forms which are not a part of their immediate communicate experience.The study of relationships between literature and advertising presumes deep understanding of their location in a cultural practice.Contemporary advertising genre widely uses scriptural matrixes of completely different discursive genres. Particular preference is given to pastiche and parody.In considering the phenomenon of modern rewriting one should not claim the decision of a difficult problem of pastiche definition. It is more necessary to emphasize valorization of such processes as imitation and transposition assuming the relation of traditions to new conceptions in French context.Pastiche should be considered as a practice which allows inquiring genre borders. This practice takes the form of a game intended to participation of an advertising message receiver.Beginning from the point of emergence pastiche became a part of social and institutional universe, the same piece of work and any other. In contemporary advertising the usage of pastiche is allowed in the name of free expression on condition that the risk of the fusion with hypotext is absent as well as an imitator has a humorous plan excluding either intention or possibility to harm anybody.The article concerns the demonstration of didactical usage efficiency of secondary literary genre, pastiche, in an intertextual practice of advertising media discourse.The emergence of this form of imitation in the course of the French language learning as a foreign one is an original means of a traditional pedagogical practice renovation of text imitation and, at the same time, the increase of learner’s motivation with the help of amusing live contact with various discursive genres.